2019
DOI: 10.1002/iub.2152
|View full text |Cite
|
Sign up to set email alerts
|

Serous IFNA3 predicts unfavorable prognosis in lung cancer via abnormal activation of AKT signaling

Abstract: This study addresses the demand through datamining The Cancer Genome Atlas (TCGA) database and elucidates mechanistic involvements of interferon alpha 8 (IFNA8) in lung cancer. The overall survival and disease-free survival of lung cancer patients in respect to IFNA8 expression level were analyzed. IFNA8 expression levels in both serum and tumor tissue were determined by real-time polymerase chain reaction. The diagnostic value of serous IFNA8 in lung cancer was assessed by receiver operating characteristic (R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This controversy might be related to the molecular pathogenesis of CML in case of gain of resistance to TKI or nilotinib not perfectly targeting all leukemic cells. As another possibility, in a current study by Ge Q, IFNA8 has been reported to be aberrantly activated in the AKT pathway (32); thus an AKT inhibitor cotreatment might be an alternative approach in nilotinibbased CML treatment since IFNA8 is a positive regulator of peptidyl-serine phosphorylation of STAT proteins (33). The expression of genes associated with immune system regulation, especially IFNA17 was significantly related to prognostic markers for disease-specific survival, and IFNA17 was down-regulated in many types of cancer (34).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This controversy might be related to the molecular pathogenesis of CML in case of gain of resistance to TKI or nilotinib not perfectly targeting all leukemic cells. As another possibility, in a current study by Ge Q, IFNA8 has been reported to be aberrantly activated in the AKT pathway (32); thus an AKT inhibitor cotreatment might be an alternative approach in nilotinibbased CML treatment since IFNA8 is a positive regulator of peptidyl-serine phosphorylation of STAT proteins (33). The expression of genes associated with immune system regulation, especially IFNA17 was significantly related to prognostic markers for disease-specific survival, and IFNA17 was down-regulated in many types of cancer (34).…”
Section: Discussionmentioning
confidence: 95%
“…Especially IFNA7 is upregulated in leukemia as regulating interferon signaling and also JAK/STAT signaling thus should be downregulated (31). Among those that we analyzed, only IFNA8 expression was increased, whereas its immunogenomic structure was reported to have an association with survival (32). This controversy might be related to the molecular pathogenesis of CML in case of gain of resistance to TKI or nilotinib not perfectly targeting all leukemic cells.…”
Section: Discussionmentioning
confidence: 97%